2021
DOI: 10.1371/journal.ppat.1009405
|View full text |Cite
|
Sign up to set email alerts
|

Sequential targeting of interferon pathways for increased host resistance to bacterial superinfection during influenza

Abstract: Bacterial co-infections represent a major clinical complication of influenza. Host-derived interferon (IFN) increases susceptibility to bacterial infections following influenza, but the relative roles of type-I versus type-II IFN remain poorly understood. We have used novel mouse models of co-infection in which colonizing pneumococci were inoculated into the upper respiratory tract; subsequent sublethal influenza virus infection caused the bacteria to enter the lungs and mediate lethal disease. Compared to wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
(84 reference statements)
0
18
0
Order By: Relevance
“…Type-II IFN elaborated later in the IAV infection process alters the function and phagocytosis capacity of AM, which then fuels the growth of bacteria and uncontrolled tissue damage [43,50,90]. The continual replication of bacteria results in recruitment of inflammatory cells to the lung and weakens the repair process [50,90,91]. These results implicate host IFN responses during IAV infection in enhancement of secondary bacterial infection.…”
Section: Interferons (Ifns)mentioning
confidence: 93%
See 3 more Smart Citations
“…Type-II IFN elaborated later in the IAV infection process alters the function and phagocytosis capacity of AM, which then fuels the growth of bacteria and uncontrolled tissue damage [43,50,90]. The continual replication of bacteria results in recruitment of inflammatory cells to the lung and weakens the repair process [50,90,91]. These results implicate host IFN responses during IAV infection in enhancement of secondary bacterial infection.…”
Section: Interferons (Ifns)mentioning
confidence: 93%
“…Others have instead defined a critical role of type II IFN [39,40,[47][48][49] and direct inhibition of AM-mediated bacterial clearance. In our recent study we observed that influenza co-infection caused IFN-dependent inflammation that facilitated spreading of the colonizing bacteria into the lungs, followed by tissue damage and death [50]. Understanding the pathways responsible for co-infection during influenza has been complicated by several confounding factors.…”
Section: Inflammation In Co-infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…72 Influenza infection might also impair regulatory mechanisms of innate and adaptive immune systems that do not suppress bacterial growth and promote superinfection. 135,136 Influenza infection-mediated breakdown in the lung barrier function increases risk of bacterial coinfection, but co-infections might also occur with milder disease pathology triggering host cytokine pathways. Thus, if milder infections also promote bacterial pneumonia without direct lung damage, the chances of attenuating bacterial pneumonia are less likely without blocking infection.…”
Section: Acute Lung Injury Subphenotype Might Be Most Amenable To Immunoattenuationmentioning
confidence: 99%